Transformasi Koordinat Bola Langit Ke Dalam Segitiga Bola (Equatorial Dan Ekliptika) Dalam Penentuan Awal Waktu Salat - Muthmainnah Muthmainnah (Universitas Cokroaminoto Yogyakarta, 2015)
There are four coordinate systems to determine the position of celestial bodies, namely: horizon coordinate system, equatorial coordinate system, the clock angle coordinate system and the ecliptic coordinate system. The crucial point to ask is the way to connect between those coordinate systems and how does it work. The way to connect between the coordinate system is called transformation. Celestial coordinate transformation from one coordinate system to another coordinate system can be done by using the spherical triangle formulas or using the rotation matrix. Both ways of coordinate transformation are essentially the same. This paper discusses the celestial coordinate transformation into a spherical triangle for determining the starting time of prayer. The focus of the study is limited and technically directed to dissect the transformation of the ecliptic geocentric (No. 2) to the equatorial geocentric (No. 3) and vice versa. The author concludes that the sky spherical coordinate system is the basis of reference to determine the position of celestial objects. The results of the transformation in the spherical triangle formula obtained sin, cos and tangent. These are actually the three forms of data which are useful to calculate the times on earth, including the time of prayer. Position of a star (in this case the sun) is very important in the beginning of the prayer time calculations because the data required are; the declination calculation, the height of the sun, and the sun angle. Besides, transformation also calculates the ecliptic longitude ecliptic latitude, the longitude of the sun. Position of the sun can also be used to calculate the direction of Qibla, the initial determination moon and eclipse. Thus, this transformation turned out to be a staple in subsequent calculations.